Female Entrepreneurship in Kazakhstan - Krystyna GOMOLKA (Communications of International Proceedings, 2021)
Women constitute the majority of the Kazakh population and, even though they live almost 10 years longer than men on average, they are far less economically active. Less than half of the female population take up employment. Women’s wages are often as much as 30% lower than men’s. The subjective reasons for undertaking economic activity as mentioned by women included: independence from the husband, low earnings of the husband and wish to help the family, lower pay compared to men’s, and opportunities in business. Wishing to encourage women to undertake economic activity, the government of Kazakhstan adopted the Act on gender equality, followed by a programme of intensified efforts for SME development. Women’s entrepreneurship was supported by funds made available as part of financial programmes aimed at women, the most important of which is known as DAMU. In 2009 companies with female managers accounted for 5.17% and in 2019 for 43.26% of all SMEs. The majority of the businesses established by women were in the services, retail and wholesale sectors. Car and motorcycle repair enterprises and other services employed the largest number of workers. The largest number of companies were established in two cities: Almaty and Nur-Sultan. The businesses owned by women were mostly one-person companies.
Keywords: Kazakhstan; entrepreneurship; women; SME; DAMU Fund.